Revitalisasi Nilai Kemanusiaan yang Adil dan Beradab dalam Upaya Mencegah Diskriminasi Agama di Lingkungan Fakultas Pendidikan Bahasa dan Sastra - Anjani Dwi Maharani Priatna; Calmelia Nadhire Alfisyahr; Fathirezi Khairi Hermawan; Ibnaty Rafaeylah Muyassarah; Zara Sajidah Iman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2026)
This research examines religious discrimination in the Faculty of Language and Literature Education environment and aims to revitalize fair and civilized humanistic values in preventing religious discrimination. The method used is qualitative descriptive, understanding social phenomena in depth through interviews. The research shows students’ perspectives on religious discrimination and the application of fair and civilized humanistic values. This research concludes that religious tolerance in the Faculty of Language and Literature Education environment is already running well, but in practice, there is still subtle discrimination in the form of certain stereotypes. This causes discomfort for minority students and requires campus support to create a fair and comfortable environment in appreciating diversity.